Two Distinct Monooxygenases for Alkane Oxidation in Nocardioides sp. Strain CF8 - Hamamura, Natsuko (American Society for Microbiology, 2001)
Alkane monooxygenases in Nocardioides sp. strain CF8 were examined at the physiological and genetic levels. Strain CF8 can utilize alkanes ranging in chain length from C(2) to C(16). Butane degradation by butane-grown cells was strongly inhibited by allylthiourea, a copper-selective chelator, while hexane-, octane-, and decane-grown cells showed detectable butane degradation activity in the presence of allylthiourea. Growth on butane and hexane was strongly inhibited by 1-hexyne, while 1-hexyne did not affect growth on octane or decane. A specific 30-kDa acetylene-binding polypeptide was observed for butane-, hexane-, octane-, and decane-grown cells but was absent from cells grown with octane or decane in the presence of 1-hexyne. These results suggest the presence of two monooxygenases in strain CF8. Degenerate primers designed for PCR amplification of genes related to the binuclear-iron-containing alkane hydroxylase from Pseudomonas oleovorans were used to clone a related gene from strain CF8. Reverse transcription-PCR and Northern blot analysis showed that this gene encoding a binuclear-iron-containing alkane hydroxylase was expressed in cells grown on alkanes above C(6). These results indicate the presence of two distinct monooxygenases for alkane oxidation in Nocardioides sp. strain CF8.